2013
DOI: 10.3389/fpsyg.2013.00741
|View full text |Cite
|
Sign up to set email alerts
|

Emotional sounds modulate early neural processing of emotional pictures

Abstract: In our natural environment, emotional information is conveyed by converging visual and auditory information; multimodal integration is of utmost importance. In the laboratory, however, emotion researchers have mostly focused on the examination of unimodal stimuli. Few existing studies on multimodal emotion processing have focused on human communication such as the integration of facial and vocal expressions. Extending the concept of multimodality, the current study examines how the neural processing of emotion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 66 publications
(92 reference statements)
4
30
0
Order By: Relevance
“…Indeed, some evidence suggests that the processing of non-verbal emotional auditory stimuli can enhance early visual processing in the form of enhanced amplitudes in the P1 component (e.g. Brosch et al, 2009;Gerdes et al, 2013). Similar to affective prosody, affective semantics may increase the salience of the emotional stimuli and elicit an analogous longer lasting posterior ERP effect in the P1 range.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, some evidence suggests that the processing of non-verbal emotional auditory stimuli can enhance early visual processing in the form of enhanced amplitudes in the P1 component (e.g. Brosch et al, 2009;Gerdes et al, 2013). Similar to affective prosody, affective semantics may increase the salience of the emotional stimuli and elicit an analogous longer lasting posterior ERP effect in the P1 range.…”
Section: Discussionmentioning
confidence: 99%
“…de Gelder and Vroomen, 2000) already during early perceptual processing stages (e.g. de Gelder et al, 1999;Gerdes et al, 2013;Pourtois et al, 2000Pourtois et al, , 2002Stekelenburg and Vroomen, 2007) probably involving specialized structures (e.g. de Gelder and Van den Stock, 2011), while incongruent audiovisual input can even lead to perceptual illusions (cf.…”
Section: Introductionmentioning
confidence: 99%
“…This area of research is only now emerging (e.g. [83,84]) and the NeCoPES model may offer some initial neurocognitive insights.…”
Section: Discussionmentioning
confidence: 99%
“…Watson et al (2013) showed that audiovisual integration areas of the superior temporal cortex are sensitive to emotional congruency: Conflicting affective information enhanced activity in these sensory integration areas. Stronger cortical processing of incongruent emotional stimuli was also reported by Gerdes et al (2013). They found enlarged P100 and P200 components for conflicting emotional information.…”
mentioning
confidence: 54%
“…In a similar way, auditory emotional cues can enhance early cortical processing of visual stimuli. Gerdes et al (2013) found an amplitude modulation of early visual P100 and P200 components when pictures were accompanied by emotional sounds. Emotional "crosstalk" between early auditory and visual areas thus seems to exist in both directions.…”
mentioning
confidence: 91%